Autonomy or Exploitation? - Esau, Darren (The Hastings Center report, 2013)
An eighty-six–year-old woman has had lifelong obsessive-compulsive disorder. At times, it has been so severe that she has lost touch with reality and been psychotic. She is actively followed by a community mental health nurse. Since she is physically frail, the nurse visits her at home and liaises with the attending psychiatrist, who adjusts medications as needed. Currently, the patient is stable, and there is no evidence of psychosis. The patient's home deteriorates, and several repairs are needed. The nurse questions the patient about this, and the patient agrees to have her nephew arrange for the repairs and pay for them out of her bank account. The nurse asks how the nephew has access to the account. The patient mentions that he has power of attorney, but when asked to supply the document giving him this authority, she becomes confused and supplies a number of bank statements instead. The nurse is surprised to see several withdrawals for over ten thousand dollars each. When she questions the patient about these, the patient simply suggests that her nephew must have “needed the money” for something. The nurse questions her repeatedly about this matter, but she refuses to give further details. The patient becomes quite upset whenever the nurse brings it up and states, “This is my money, and he wouldn't take it unless he needed it to help me.” Should the nurse challenge the patient's right to make her own financial decisions in order to avoid a risk of exploitation by her family members? Does the patient have the right to refuse a capacity assessment, which could determine her decision-making abilities in this area?